Corporate governance and corporate social responsibility: The case of small, medium, and large firms - Sajid Gul; Faqir Muhammad; Abdul Rashid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
This paper aims to explore whether and how firm-level governance mechanisms affects Corporate Social Responsibility (CSR) using a large sample of firms listed at Pakistan Stock Exchange. Further, the paper investigates the differential effects of corporate governance (CG) on CSR across small, medium, and large firms. The findings strongly support the hypothesis that CG alone is not sufficient to induce firms to provide more CSR information. Rather, we show that both CG and ownership structure matters and have a vital role to play in firms' choice of CSR engagement. The results reveal that better governed firms have higher CSR disclosure when compared with lower CG firms controlling for the level of insider ownership. Specifically, the results suggest that firms are more likely to be involved in CSR when insiders' ownership is at medium level (25% to 50%) as compared to low (0 to 25%) or high level (>50%). Nonetheless, the estimates suggest that CSR involvement decreases when the insider ownership goes beyond the 50% level. Finally, the results reveal that there are significant differences in the effects of CG and other underlying empirical determinants of CSR across different sized firms.
Keywords: 330; corporate social responsibility; corporate governance; insiders' ownership; system GMM